Endometrial glycodelin-A expression in the luteal phase of stimulated ovarian cycles - Brown, Samuel E; Mandelin, Erik; Oehninger, Sergio; Toner, James P; Seppala, Markku; Jones, Howard W (Fertility and sterility, 2000)
Objective: To determine if controlled ovarian hyperstimulation (COH) affects the endometrial expression of glycodelin-A (GdA). Design: Prospective, controlled study. Setting: Tertiary infertility clinic. Patient(s): Fifteen oocyte donors undergoing COH cycles and 19 natural-cycle control patients. Intervention(s): COH, endometrial biopsies. Main Outcome Measure(s): Immunohistochemical scoring of endometrial GdA expression, morphologic endometrial dating, and serum E 2, LH, and P 4 concentrations. Result(s): GdA was detected in all subjects throughout the implantation window period. Immunolocalization was demonstrated in the endometrial glands and not in the stroma or on the surface. A significantly increased proportion of GdA-staining endometrial cells were noted in COH cycle patients as compared with natural-cycling control patients throughout the window of embryo implantation. Both cycle types demonstrated increasing GdA expression throughout the late luteal phase. A significant positive correlation was noted between GdA expression and serum E 2 levels (r = 0.5, P<.001) in natural cycles and advanced histology in COH cycles (r = 0.63, P=.01). Neither LH nor P 4 were correlated with endometrial GdA expression. Conclusion(s): COH cycles have a significantly increased endometrial GdA expression throughout the implantation phase of the luteal cycle when compared with normal menstrual cycles. The increased expression may affect implantation during COH cycles.